Missing Daughter - Kiersten Modglin (London EC4Y DZ Bookouture, 2021)
"My husband says I've been struggling since Skylar was born and that sometimes I forget things. But I remember every moment of my daughter's party-including him locking the door after our family and friends left. Yes, we both had a drink and I slept heavily but I know I would have heard my child cry. A good mother always does. My therapist says I need to stand up for myself. She wants me to confront my husband about the woman I heard him talking to the other night when he thought I was asleep. And about the child's toy that I found that does not belong to Skylar. Is he hiding something? But as the hours race by I soon realize I was totally wrong about everything that happened that night. I thought I'd put my past behind me long ago but I was wrong. All I know is this: I'll do whatever it takes to save my child. Will you believe me?" --Page 4 of cover